S101 Single centre experience of switching patients with idiopathic pulmonary fibrosis from pirfenidone to nintedanib. (15th November 2016) - Rathnapala, A; Fries, A; Ruggiero, C; Ho, LP; Hoyles, RK
Abstract : Background: Idiopathic Pulmonary Fibrosis (IPF) is a progressive disease with an average life expectancy of 2–4 years. The anti-fibrotic agents Nintedanib and Pirfenidone slow disease progression, and are routinely prescribed by specialist ILD centres. Choice of agent is guided by patient and physician preference, and potential tolerance of side effects. Our centre has prescribed Nintedanib since March 2015, and Pirfenidone since 2013. Objectives: To identify the reasons driving a change of anti-fibrotic from Pirfenidone to Nintedanib, and the frequency of reported side effects and specialist nursing input before and after the switch. Methods: This retrospective study examined patients who had been switched from Pirfenidone to Nintedanib (March 2015–July 2016), including patients with >1 month duration of each agent. Data was taken from patient records including nursing advice via the ILD nurse-led helpline. Results: We identified 16 patients, with a mean duration of Pirfenidone 9 (1–30) months prior to the switch, and 8 (2–15) months Nintedanib use. Average age 73 (65–84) years, male:female 14:2, definite: probable IPF 11:5, median duration since IPF diagnosis 27 (8–65) months, median %FVC 75 (62–90) at initiation of Pirfenidone, and 68 (53–85) %FVC at initiation of Nintedanib. Rationale for switch. Disease progression (n = 5): decline in FVC ≥ 10% over one year (n = 3), acute exacerbation (n = 2). Intolerable side effects (n = 11): fatigue (3), diarrhoea (2), nausea(2), appetite or weight loss (2), skin rash (1), mood disturbance (1). Impact of switch on side effects and nursing contact. In 9 months before the switch, 13 patients made 1.5 (mean) calls (range 1–3) to the ILD helpline for advice on Pirfenidone side effect management. After the switch, over 8 months, 3 patients made 2 (mean) contacts (range 1–3) for Nintedanib related side effects (diarrhoea). Of 5 patients switched to Nintedanib for disease progression, 3 had follow up for six months, showing >10% improvement in the%FVC (n = 1), stability (n = 1), persistent mild decline ( < 5%) %FVC (n = 1). Conclusions: This study illustrates the potential of Nintedanib as an alternative for those who have disease progression despite Pirfenidone; there is good tolerance to Nintedanib with none of this cohort having to stop treatment due to side effects.